Heparin at low concentration acts as antivenom against Bothrops jararacussu venom and bothropstoxin-I neurotoxic and myotoxic actions - Rostelato-Ferreira, Sandro (Library Publishing Media, 2010)
Heparin has been shown to antagonize myotoxic effects of crotaline venoms. Here a very low heparin concentration (LHC) was examined in its ability to antagonize the neurotoxic/myotoxic effects of Bothrops jararacussu venom and its phospholipase A(2) myotoxin, bothropstoxin-I (BthTX-I), in an in vitroz nerve-muscle preparation and in mice gastrocnemius. Normalization of results was done by assays with commercial antibothropic antivenom (CBA). LHC (1IU/ml) added to the incubation bath reduced by 4- and 4.5-fold (vs 2.8- and 2.5-fold by CBA) the neuromuscular paralysis, by 5.4 and 4.4-fold (vs 2.5- and 13.3-fold by CBA) the percentage of fibers damaged and by 6- and 1.7-fold (vs 30- and 1.6-fold by CBA) the CK activity induced by B. jararacussu and BthTX-I, respectively. Protamine sulphate added 15min after the incubation of the preparation with LHC+venom, avoided the LHC neutralizing effect against venom neurotoxicity. This strongly attests that given the polycationic nature of protamine, it probably complexed with the polyanionic heparin making it unattainable for binding to basic components of venom, reducing toxicity. Since heparin antagonism is generally stronger against venom effects than is myotoxin we discuss that other venom components than the BthTX-I are likely target for the antagonism promoted by the polyanionic heparin.